Prospective study of asbestos-related diseases incidence cases in primary health care in an area of Barcelona province - Orriols Ramon; Gallego Miguel; Cantarell Gloria; Krier Ilona; García-Allas Isabel; Martínez-Artés Xavier; Tarrés Josep; Abós-Herràndiz Rafael; Rosell-Murphy Magdalena; Albertí Constança (BMC, 2010)
Abstract Background Asbestos related diseases include a number of conditions due to inhalation of asbestos fibres at work, at home or in the environment, such as pleural mesothelioma, asbestosis and calcified pleural plaques. Few epidemiological studies have established the incidence of asbestos related diseases in our area. The present proposal is based on a retrospective study externally funded in 2005 that is currently taking place in the same area and largely carried out by the same research team. The aim of the study is to achieve a comprehensive and coordinated detection of all new cases of Asbestos Related Diseases presenting to primary care practitioners. Methods/design This is a multicentre, multidisciplinary and pluri-institutional prospective study. Setting 12 municipalities in the Barcelona province within the catchment area of the health facilities that participate in the study. Sample This is a population based study, of all patients presenting with diseases caused by asbestos in the study area. Measurements A clinical and epidemiological questionnaire will be filled in by the trained researchers after interviewing the patients and examining their clinical reports. Discussion Data on the incidence of the different Asbestos Related Diseases in this area will be obtained and the most plausible exposure source and space-time-patient profile will be described. The study will also improve the standardization of patient management, the coordination between health care institutions and the development of preventive activities related with asbestos exposure and disease.